Inpatient satisfaction with nursing care in a backward region: a cross-sectional study from northwestern China - Xiaoying Wang; Juxia Zhang; Limei Yang; Jiao Dai; Wenjing Shan; Jiancheng Wang (BMJ Open)
Objectives The aim of the study was to examine the level of patient satisfaction with nursing care and identify the factors affecting satisfaction from the inpatient’s perspective in a backward region of China.Design This was a cross-sectional study.Setting The study was conducted at a tertiary hospital located in northwest China.Participants Patients admitted to the ward for at least 48 hours were chosen to participate in the survey.Primary outcome measure The Newcastle Satisfaction with Nursing Care Scale was used. Data were collected from 219 patients.Results The overall inpatient satisfaction with nursing care was 78.15±4.74. Patients were more satisfied with nurses who respected their privacy and treated them as individuals (67.7%). Patients were least satisfied with the type of information nurses gave them (11.7%) and with the sufficient awareness of their needs. Patients who were married, had a history of hospitalisation, surgery and were taken charge of by junior nurses had higher satisfaction.Conclusions The overall level of patient satisfaction was moderate. Patient-centred individualised care and providing sufficient information model of care are needed. There was a need for nurses to be aware of patients’ individualised care needs and to provide them with more information. This study may suggest/urge hospital administrators, policymakers and nurses to be more sensitive with patients’ married status, history of hospitalisation and surgery, the professional title of in charged nurses when care is provided. Ultimately to achieve better outcome of patients’ hospitalisation.